Epibenthic and Demersal Fish Community Structure and the Effects of Environmental Conditions in the Sub-Arctic Fjords Vengsøyfjorden and Kaldfjorden - Dugan, Susan Frances (UiT Norges arktiske universitet, 2020)
Epifauna are organisms that live on, or close to, the sediment surface and commonly consist of taxa such as sea anemones, sea/brittle stars, and crustaceans. These communities have an important role in redistributing and remineralizing marine organic matter, and as prey for commercially important shellfish and fish. The structure of epibenthic communities can be important indicators of anthropogenic pollution and its environmental impact. Demersal fish are also important to the benthic ecosystem as both predator and prey creating a link between pelagic and benthic ecosystems. Epibenthic communities of sub-Arctic fjords have been poorly studied, resulting in a lack of knowledge on their structure. Despite this, sub-Arctic fjords in Norway are heavily used for fisheries, aquaculture and recreation. To address this lack of information, this study investigates the biodiversity, density and structure of epibenthic fauna and demersal fish communities, and the environmental drivers affecting community structure in two fjords located in the Troms region of northern Norway (Kaldfjorden and Vengsøyfjorden). Images were collected using a drop camera in December 2017 and corresponding bottom trawls were conducted in April 2019. Images were analyzed to quantify the epibenthic community using the annotation software Biigle 2.0 – Browsing and Annotation Large Marine Image Collection. Multivariate analysis was applied to examine epifaunal community structure between the fjords and the effects of the environmental factors temperature, salinity, depth, and substrate composition. A total of 67 taxa and 11 phyla were identified in the images; 44 taxa and 6 phyla were identified in the trawls. Dominant phyla by taxon numbers included Chordata, Mollusca and Echinodermata; the dominate phyla by density were Chordata, Arthropoda and Echinodermata. Mean density estimates of epifauna ranged from 0.009 individuals per m2 (images) and from 0.047 to 0.096 individuals per m2 (trawls). The epibenthic communities were found to be significantly ...